HOW BBC CONSTRUCTS TRUTH: TRANSITIVITY AND MODALITY IN SUDAN CONFLICT - Hanifah Oktarina; Syihabuddin; Mahardhika Zifana (Lantern: Journal of Language and Literature, 2026)
The Sudan civil war, designated by the United Nations as the world's largest humanitarian crisis, has generated extensive international media coverage yet remains critically under-examined in discourse scholarship regarding how conflict knowledge is constructed and whose voices are authorized to define truth. This study employs Systemic Functional Linguistics (SFL) integrated with Critical Discourse Analysis to investigate how BBC Indonesia and BBC International construct agency distribution and epistemic authority in explainer articles about the Sudan conflict. Through qualitative transitivity and modality analysis of two comparable November 2025 articles, this research examines how linguistic choices reveal ideological positioning regarding who acts, who suffers, and whose knowledge counts as legitimate. Findings demonstrate systematic patterns across both outlets which are passive constructions and nominalization obscure military actors' responsibility for civilian casualties; asymmetric agency attribution constructs RSF as violent aggressors while rendering structural dimensions invisible; and a three-tier epistemic hierarchy privileges Western institutional voices (US, HRW) with definitive modality, grants international bodies (UN) investigative authority, while relegating local Darfuri voices to subjective belief-based positioning. Critically, these patterns converge regardless of outlets' geographic positioning, Indonesian regional versus British global, revealing what Foucault identifies as "capillary power": the circulation of Western-centric knowledge frameworks through institutionalized journalistic norms that transcend individual bias or national interest. This convergence demonstrates that transforming conflict representation requires not merely diversifying media sources but fundamentally challenging the embedded "regimes of truth" determining whose knowledge is recognizable as legitimate in global journalism, with implications extending beyond African conflict reporting to broader questions of epistemic justice in international media